Cellulose-based hydrogel for adsorptive removal of cationic dyes from aqueous solution: isotherms and kinetics. Issue 7 (6th February 2023) - Poornachandhra, Chidamparam; Jayabalakrishnan, Rajamani M; Prasanthrajan, Mohan; Balasubramanian, Govindaraj; Lakshmanan, Arunachalam; Selvakumar, S; John, Joseph Ezra
Abstract : Nanocellulose based hydrogel beads for efficient removal and recovery of dyes from textile industry effluents. Abstract : The development of economic and recyclable adsorbents for removing pollutants from contaminated water is gaining increasing attention. Agro residue or nature-based material sourced absorbents could revolutionize the future of wastewater treatment. Hence in this study, nanocellulose was synthesized from coconut husk fiber and immobilized onto chitosan to form hydrogel beads. The BET surface area and zeta potential of the adsorbent nanocrystalline cellulose–chitosan hydrogel (NCC–CH) bead was 25.77 m 2 g −1 and +50.6 mV, respectively. The functional group analysis also confirmed that the adsorbent had functional groups appropriate for the adsorption of textile dyes. The adsorption performance of NCC–CH and also the influence of initial dye concentration, adsorbent dose, pH, and contact time was evaluated by batch adsorption studies with crystal violet (CV) and methylene blue (MB) dyes. The most favorable operational conditions achieved through I-optimal design in response surface methodology were 0.5 g NCC–CH, 1 h, 9 pH, and 60 mg L −1 for CV removal (94.75%) and 0.13 g NCC–CH, 1 h, 9 pH, and 30 mg L −1 for MB removal (95.88%). The polynomial quadratic model fits the experimental data with an R 2 value of 0.99 and 0.98 for CV and MB removal, respectively. The optimum depiction of the isotherm data was obtained using the Freundlich model for MB adsorption and Freundlich and Langmuir model for CV adsorption. The Dubinin–Radushkevich (D–R) isotherm was also a good fit to the adsorption of CV and MB dye, suggesting the physisorption due to its free energy of adsorption < 8 kJ mol −1 . The kinetics were effectively explained by a pseudo-second order model for both the dyes suggesting that chemical mechanisms influenced the adsorption of CV and MB dyes onto NCC–CH. The intraparticle diffusion model best suited the MB adsorption with three stages rather than the CV with a single step process. Also, the removal efficiency of adsorbent was retained at above 60% even after seven adsorption–desorption cycles indicating the effectiveness of the NCC–CH hydrogel beads for the removal of textile dyes.